POTENSI EKSTRAK Peperomia pellucida (L.) TERHADAP PENGHAMBATAN PERKECAMBAHAN DAN PERTUMBUHAN Mikania micrantha (K.) - Kurnia Sari; Siti Fatonah; Mayta Novaliza Isda (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Weed is one of the limiting factors of crop production. Some of weed controls use synthetic and organic herbicides. Organic herbicides are used as the environmentaly friendly weed control. One of potential plants as organic herbicides is Peperomia pellucida that contains allelopathic compound and essensial oil. The purposes of this research were to determine the effect of P. pellucida extract and the most effective and efficient extract concentration in inhibiting the germination and growth of Mikania micrantha. This research used Randomized Complete Design using four treatments, i. e. control, 7,5%, 15% and 30% of P. pellucida extracts. The collected data was analyzed using Analysis of Variance (ANOVA) and followed by Duncan’s Multiple Range Test (DMRT) if the result was significantly different. The result showed the decrease of the germination and growth of M. micrantha weed. The most effective and efficient extract was 7,5% P. pellucida extract.